Children of war: the long-run effects of large-scale physical destruction and warfare on children - Mevlude Akbulut-Yuksel (Institute for the Study of Labor (IZA), 2009)
During World War II, more than one-half million tons of bombs were dropped in aerial raids on German cities, destroying about one-third of the total housing stock nationwide. This paper provides causal evidence on long-term consequences of large-scale physical destruction on the educational attainment, health status and labor market outcomes of German children. I combine a unique dataset on city-level destruction in Germany caused by Allied Air Forces bombing during WWII with individual survey data from the German Socio-Economic Panel (GSOEP). My identification strategy exploits the plausibly exogenous city-by-cohort variation in the intensity of WWII destruction as a unique quasi-experiment. My findings suggest significant, long-lasting detrimental effects on the human capital formation, health and labor market outcomes of Germans who were at school-age during WWII. First, these children had 0.4 fewer years of schooling on average in adulthood, with those in the most hard-hit cities completing 1.2 fewer years. Second, these children were about half inches (one centimeter) shorter and had lower self-reported health satisfaction in adulthood. Third, their future labor market earnings decreased by 6% on average due to exposure to wartime physical destruction. These results survive using alternative samples and specifications, including controlling for migration. Moreover, a control experiment using older cohorts who were not school-aged during WWII reveals no significant city-specific cohort trends. An important channel for the effect of destruction on educational attainment appears to be the destruction of schools and the absence of teachers, whereas malnutrition and destruction of health facilities during WWII seem to be important for the estimated impact on health.
Keywords: I21; I12; J24; N34; 330; Physical destruction; human capital formation; children; wars; Kriegsschaden; Kinder; Bildungsniveau; Gesundheit; Erwerbsverlauf; Sozialgeschichte; Deutschland